Pengaruh Pendidikan Kesehatan Berbasis Video Animasi terhadap Pengetahuan dan Kepatuhan Suplemen Besi di Kalangan Siswa Sekolah Menengah Atas - Agus Hendra Al Rahmad; Dewi Sartika; Arnisam (NUTRIASIK: Jurnal Terapan Gizi dan Pangan Fungsional Kesehatan, 2026)
Background: Non-compliance of rematriates is one of the difficulties in preventing and overcoming anaemia Management of anaemia in rematriates with the priority of giving Blood Addition Tablets (TTD) through school institutions. One way to increase a person’s knowledge is through providing nutrition education. Nutrition education methods can be used by delivering material through counselling and by using animation media. The aim is to determine the effect of counselling using animation videos on knowledge and compliance with the consumption of blood supplement tablets (TTD) in school children at SMA Negeri 1 Meureubo Meureubo District West Aceh Regency. Methods: This research is a quantitative study that uses a Quasi Exsperimental approach. The sample was taken as many as 26 female students by total sampling. The research was conducted at SMA Negeri 1 Meureubo in January-February 2024, data collection of knowledge using questionnaires and compliance with TTD consumption using Compliance Cards, data analysis using the wilxocon test. Results: Average knowledge before and after increased with a difference of 3.54. The average TTD consumption compliance before and after increased with a difference of 1.53. The results showed that there was a significant influence between knowledge and compliance with TTD consumption before (pretest) and after (post test) with a value of (p=0.000) and (p=0.001). Conclusion: counselling using videos animation has a significant effect in increasing knowledge and compliance with TTD consumption in school children.